MODEL OF PSYCHOLOGICAL AND PEDAGOGICAL SUPPORT OF ADAPTATION OF STUDENTS AT THE INITIAL STAGE OF UNIVERSITY EDUCATION - Irina Lilienthal; Inna Kolesnikova (Вестник Северо-Кавказского федерального университета)
The central issue of the article is a practice-oriented approach, involving the development and the possibility of introducing the model of psychological and pedagogical support of adaptation of students in the learning process at the university, based on the assessment of adaptation options. The paper presents the adaptation process of ascertaining experimentfirst-year students, a model ofpsycho-pedagogical support of the educational process NCFU, conditions for its implementation, performance criteria, expected results.